Kerja Sama Militer Brunei Darussalam-Inggris dan Dampaknya terhadap Stabilitas Regional Asia Tenggara - Aflah Zahratsabitha Irwan; Imam Fadhil Nugraha (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This paper examines the military cooperation between Brunei Darussalam and the United Kingdom, as well as its impact on regional stability in Southeast Asia, focusing on Brunei's non-alignment strategy as a small state. Using a descriptive analytic method based on a literature review, this paper explores descriptive data on the dynamics of Brunei's foreign policy strategy in building bilateral relations, the role of the UK post-Brexit through the Global Britain strategy in strengthening bilateral relations with ASEAN member countries, and the implementation of Brunei and British military cooperation in maintaining regional security stability through the presence of British Forces Brunei since 1963. This is supported by historical ties and the Garrison Agreement to strengthen the security of the country and the region without confrontation. Therefore, this paper shows that Brunei has managed to balance military cooperation with the UK and economic cooperation with China in the midst of great power rivalries and tensions over the South China Sea dispute, as well as its implications for regional stability.